Pragmatisme John Dewey dan Korelasinya Dengan Anekdot - Suci Rengganis; Syihabuddin Syihabuddin (Peneliti.net, 2023)
Pragmatism is a philosophy pioneered by Charles S. Pierce and developed by William James and John Dewey. This philosophy emphasizes the practical value and usefulness of truth. One of the figures who helped develop this understanding is John Dewey who has another term for pragmatism, namely instrumentalism. He formulated three concepts in instrumentalism, namely the temporalism aspect which emphasizes real action or movement, the futurism aspect which encourages looking at the future or future, and the meliorism aspect which states that something big can be changed for the better with energy. The application of pragmatism can also be reflected in a work, one of which is an anecdote. In short, an anecdote can be referred to as a humorous story that aims to entertain its readers. The main purpose is to satirize or criticize something that is considered unbalanced or wrong in the environment. Pragmatism can be clearly reflected in the practical purpose of anecdotes when examined based on the three concepts of instrumentalism. Thus, anecdotes can be said to be true based on John Dewey's pragmatism perspective. This research is a qualitative research with library research technique. The data used is secondary data from various literatures that are in accordance with this study. The data is researched by reading and analyzing various credible and relevant literature with the object of this research study.